Enriched Environment Facilitates Anxiolytic Efficacy Driven by Deep-Brain Stimulation of Medial Prefrontal Cortex - Bhaskar, Yamini; Lim, Lee Wei; Mitra, Rupshi (Frontiers in Behavioral Neuroscience, 2018)
Deep brain stimulation is a widely used treatment for neurodegenerative disorders like Parkinson’s disease. Recently several studies have used preclinical animal models to suggest that deep brain stimulation has a potential to improve emotional symptoms in mental disorders like treatment-resistant depression and post-traumatic stress disorder. An important difference between neurodegenerative and emotional disorders is the crucial role of environment in ontogeny of the later. Thus, it is important to understand effects of deep brain stimulation in the context of environmental variation. In this study we show that deep brain stimulation of ventromedial prefrontal cortex reduces anxiety in rats when it is coupled with simultaneous exposure to enriched environment. In contrast, effects of deep brain stimulation on anxiety like behaviors remained equivocal when animals were instead housed in standard laboratory conditions. These results suggest that ability of deep brain stimulation to treat anxiety and related phenotypes can be significantly enhanced by enriched environmental opportunities.